2017
DOI: 10.2147/opth.s109247
|View full text |Cite
|
Sign up to set email alerts
|

Normal flora of conjunctiva and lid margin, as well as its antibiotic sensitivity, in patients undergoing cataract surgery at Phramongkutklao Hospital

Abstract: ObjectiveThis study aimed to evaluate the normal flora of conjunctiva and lid margin, as well as its antibiotic sensitivity.DesignThis was a prospective cross-sectional study.Patients and methodsA prospective study was conducted on 120 patients who underwent cataract surgery at the Phramongkutklao Hospital from September 2014 to October 2014. Conjunctival and lid margin swabs were obtained from patients before they underwent cataract surgery. These swabs were used to inoculate blood agar and chocolate agar pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
2
13
1
Order By: Relevance
“…The most common bacterial isolate was coagulase-negative staphylococci (76%, S. epidermidis and S. lugdunensis ). These results are consistent with those in previous reports 1,13,19 that showed coagulase-negative staphylococci to be the most common bacteria isolated from conjunctiva.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The most common bacterial isolate was coagulase-negative staphylococci (76%, S. epidermidis and S. lugdunensis ). These results are consistent with those in previous reports 1,13,19 that showed coagulase-negative staphylococci to be the most common bacteria isolated from conjunctiva.…”
Section: Discussionsupporting
confidence: 94%
“…Coagulase-negative staphylococci are the most common bacteria isolated from the conjunctiva and the lid margin. 1 Diabetes mellitus was linked with a higher rate of positive bacterial cultures of the conjunctival sac before cataract surgery. 2 It was also shown that patients with diabetes mellitus have more gram-negative bacterial cultures.…”
Section: Introductionmentioning
confidence: 99%
“…was rarely isolated from normal conjunctiva, while several studies isolated Enterococcus spp. from 2.5% to 5.2% in their cases [23][24][25][26][27]. We observed similar pattern of microorganisms population isolated from normal conjunctiva to the previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have reported positive detection rates for bacteria in lacrimal secretion samples from chronic dacryocystitis patients of 48.3-96% [5][6][7][8][9][10][11][12][13][14][15], with rates of 20.6-87.0% in normal conjunctival sac secretion samples [16][17][18]. Gram-negative bacteria were found in 12.1-48.6% of lacrimal secretion samples from chronic dacryocystitis patients and 1.7-8.9% of normal conjunctival sac secretions.…”
Section: Discussionmentioning
confidence: 99%
“…Gram-negative bacteria were found in 12.1-48.6% of lacrimal secretion samples from chronic dacryocystitis patients and 1.7-8.9% of normal conjunctival sac secretions. Similarly, anaerobic bacteria were found in 10.7-18.6% and 0-16.5% of the two types of samples, respectively [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Therefore, the results of the current study are fairly consistent with previous findings, with bacteria detected in 61.9% of the lacrimal duct secretion samples from chronic dacryocystitis patients and 50.9% of the non-infectious eye disease patients (P \ 0.05).…”
Section: Discussionmentioning
confidence: 99%